Chronic scrotal pain syndrome (CSPS): the widespread use of antibiotics is not justified. (29th October 2012) - Strebel, R. T.; Schmidt, C.; Beatrice, J.; Sulser, T.
Summary Data supporting the widespread use of antibiotics in patients with chronic scrotal pain syndrome (CSPS) are not available. Therefore, the aim of this study was to investigate the presence of bacteria in the genitourinary tract in patients presenting with CSPS. From July 2005 to July 2007 we prospectively enrolled patients presenting with CSPS in our outpatient clinic. The evaluation consisted of a detailed patient's history, physical examination and ultrasound examination of the scrotum. A blood and urinalysis, a Meares‐Stamey four‐glass test for bacterial cultures and PCR testing for Chlamydia trachomatis, Ureaplasma urealyticum, Mycoplasma hominis and Neisseria gonorrhoeae as well as a semen culture were performed. We assessed the symptom severity with the chronic epididymitis symptom index (CESI) score according to Nickel et al. (J Urol 2002, 167:1701; based on the NIH‐CPSI). A total of 55 eligible men (median age 34 years) with CSPS were enrolled in the study. The median CESI score was 17 (range 4–26). The majority of patients (n = 39; 71%) were seen by a general practitioner or an urologist before. Of these, 25 patients (64%) were treated with antibiotics and 26 (67%) with non‐steroidal anti‐inflammatory drugs, respectively. A significant bacterial colony count in at least one specimen was detected in 21 of 55 patients (38%). The predominantly detected microorganisms were an Alpha‐haemolytic Streptococcus (11 patients) and coagulase‐negative staphylococci (10 patients). Thus, only in 12 of 55 (22%) patients isolated bacteria were considered to be of clinical relevance. No factor or condition predictive for a bacterial aetiology for CSPS could be identified. In our microbiological assessment of patients presenting with CSPS we found no evidence for the widely held belief that CSPS is predominantly the result of a chronic bacterial infection. We therefore conclude that the widespread use of antibiotic agents in the treatment of patients with CSPS is not justified.